2008
DOI: 10.1007/s00403-008-0912-8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of itch-associated scratch behavior to the development of skin lesions in Dermatophagoides farinae-induced dermatitis model in NC/Nga mice

Abstract: Recently, we have reported that the pathophysiological features of dermatitis induced by the repeated application with Dermatophagoides farinae (Df) extract ointment in NC/Nga mice were similar to those observed in the patients with atopic dermatitis. In the present study, we first examined whether the application of Df in other mouse strains could induce dermatitis. The repeated application of Df body (Dfb) ointment to the barrier-disrupted back of ICR, C57BL/6, and Balb/c mice did not cause any apparent skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…In addition, a single dose of S-777469 suppressed the nerve fiber sprouting into the epidermis 24 h after the administration of mite antigen in a mouse model of atopic dermatitis (data not shown). Moreover, we reported that cutting of toenails suppressed mite antigeninduced skin inflammation in NC/Nga mice [34] . Therefore, it is possible that the anti-inflammatory effects of S-777469 are partially mediated by the inhibition of pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a single dose of S-777469 suppressed the nerve fiber sprouting into the epidermis 24 h after the administration of mite antigen in a mouse model of atopic dermatitis (data not shown). Moreover, we reported that cutting of toenails suppressed mite antigeninduced skin inflammation in NC/Nga mice [34] . Therefore, it is possible that the anti-inflammatory effects of S-777469 are partially mediated by the inhibition of pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…The subclinical macroscopic observations were made using the methods of Yamamoto et al [18]. The total clinical skin score for the AD-like lesions on the NC/Nga mice was defined as the sum of individual scores, graded as 0 (none), 1 (mild), 2 (moderate), or 3 (severe), for each of four signs and symptoms (erythema/hemorrhage, scarring/ dryness, edema, excoriation/erosion) on the back skin.…”
Section: Methodsmentioning
confidence: 99%
“…Representative images were also captured using a handscope (X50; AT Trading). In the final week of the experimental period, clinical evaluation was performed with the unaided eye using the Yamamoto et al (15) method, which is a standard method for evaluation of atopic dermatitis. Skin was evaluated according to the 4 categories of erythema/hemorrhage, dryness/scaling, edema, and excoriation/erosion.…”
Section: )mentioning
confidence: 99%
“…Observations were made over the course of 3 weeks with a 1 week interval. Clinical skin scores (15) were measured for experimental and control group mice. Representative images were also captured using a handscope (X50; AT Trading).…”
Section: )mentioning
confidence: 99%